2007
DOI: 10.1111/j.1600-0404.2006.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of executive functions in obstructive sleep apnea syndrome

Abstract: Objectives –  To provide an update on recent research concerning obstructive sleep apnea syndrome (OSAS) and executive functions. Methods –  A systematic review was carried out on reports drawn from MEDLINE and PSYCHLIT (January 1990–December 2005) and identified from lists of references in these reports. The selection criteria were met by 40 articles. Results –  The sample sizes in the reviewed studies varied widely and consisted mostly of selected groups. Most patient samples were heterogeneous in terms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 53 publications
(318 reference statements)
5
100
0
4
Order By: Relevance
“…One study conducted in Finland with 40 newly diagnosed OSA cases and 20 healthy controls also found impaired performance of the former in some neuropsychological tests, such as the copy of the Rey figure, Block Design and Trail Making B 24 . In a subsequent study, this same group of investigators demonstrated that even prolonged CPAP treatment was not able to match the performance of both groups, especially in learning tasks 25 .…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted in Finland with 40 newly diagnosed OSA cases and 20 healthy controls also found impaired performance of the former in some neuropsychological tests, such as the copy of the Rey figure, Block Design and Trail Making B 24 . In a subsequent study, this same group of investigators demonstrated that even prolonged CPAP treatment was not able to match the performance of both groups, especially in learning tasks 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have assessed OSAS patients’ executive functions with only 1 or 2 tests; this is not enough to draw generalizable conclusions about executive functions in OSAS [15]. Only a few previous studies have assessed executive functions more comprehensively [16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…OSAS has been recognized as a significant problem associated with a wide range of physical and psychological consequences, including hypertension, increased risk of vascular disease and accident, depression, poor quality of life, attention deficit, poor alertness and cognitive problems [2][3][4][5][6]. The most common cognitive problems reported in OSAS patients are deficit on attention, memory and learning abilities, motor performance, constructional abilities and executive functions [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the compliance of CPAP treatment in most sleep center is as low as 30-60 % [8]. The effects of CPAP treatment on the cognitive function are controversial with various results [2,4,[9][10][11]. Various CPAP compliances, different measurement tools and condition are factors confounding these results [9].…”
Section: Introductionmentioning
confidence: 99%